The Role of Technology in English Language Learning: A Quantitative Examination of Student Performance Engagement and Motivation - Nasution, Dina Syarifah (West Science Interdisciplinary Studies, 2023)
Using a quantitative methodology, this study examined the effects of academic achievement, student motivation, and engagement on the use of technology in English language instruction at a high school in North Sumatra, Indonesia. A sample of 200 students was examined using Structural Equation Modeling with Partial Least Squares (SEM-PLS) in order to investigate the relationship between academic achievement, student engagement, motivation, and technology integration. The findings showed a strong correlation between academic performance, motivation, and engagement with technological integration. A mediation analysis revealed how important student motivation and engagement are in bridging the gap between technology and academic achievement. The results of the bootstrapping study were more reliable, and the proposed model's explanatory strength and predictive significance were highlighted by the R2 and Q2 values. There includes a discussion of the implications for English instruction, along with some helpful suggestions and directions for further investigation.